In-service Teacher Education for Primary and Secondary School Teachers - Sindkhedkar, S. D. (THE PRIMARY TEACHER, 2006)
Education is the main course, which affects the quality of life. It gives real meaning to democracy in which a common man participates and contributes effectively to change and development. Education on which human progress depends on to such a large extent is being given a major consideration—all factors, which determine the quality of national development. Teachers occupy an unchallengeable position in the educational process. They play a vital role in the all round development of the personality of children by exercising a personal influence. Every country develops its system of education to meet the challenges of changing times. Education plays a vital role in the development of human potential. Taking into consideration the challenges of the near future, the Government of India has published its National Educational Policy in 1986 to meet the challenges. Many innovative and new ideas have been included in the policy. The policy advocates equal opportunities to all, both in terms of access to education, conditions of success, common education structures, a national curriculum framework, minimum levels of learning for each stage of education.